2015
DOI: 10.18378/rvads.v10i4.3416
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de Cerveja Artesanal com Acerola (Malpighia emarginata DC) e Abacaxi (Ananas comosus L. Merril)

Abstract: <p>A cerveja é a bebida alcoólica mais consumida no mundo. Estando bem relacionado com festividades e comemorações, porém essa bebida contém uma variedade de compostos bioativos, vitaminas e minerais, capazes de promover benefícios quando a sua ingestão é feita de maneira moderada. O mercado está a cada dia buscando produtos diferenciados e até exclusivos, surge assim o campo das cervejas artesanais. O objetivo deste trabalho foi desenvolver uma cerveja artesanal com acerola e abacaxi, trazendo uma nova … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 0 publications
5
8
1
13
Order By: Relevance
“…The pH of the beers analyzed was situated between 3.47 and 4.98, in accordance with Rebello (2009), who states beer has a pH of around 4.0. Results similar to those found for the Pós Beer developed in this work (4.46) were reported by Matsubara et al (2016), which found a pH of 4.27 for wheat craft beer with ginger, as well as by Pinto et al (2015), with pH of 4.24 for craft beer with acerola and pineapple.…”
Section: Physicochemical Characterizationsupporting
confidence: 90%
See 3 more Smart Citations
“…The pH of the beers analyzed was situated between 3.47 and 4.98, in accordance with Rebello (2009), who states beer has a pH of around 4.0. Results similar to those found for the Pós Beer developed in this work (4.46) were reported by Matsubara et al (2016), which found a pH of 4.27 for wheat craft beer with ginger, as well as by Pinto et al (2015), with pH of 4.24 for craft beer with acerola and pineapple.…”
Section: Physicochemical Characterizationsupporting
confidence: 90%
“…The beer with ginger presented generally good sensory acceptance of visual aspects such as color and appearance, in addition to flavor and aroma. The notes obtained in this study were higher than those reported by Costa (2016) for the same sensory attributes, except for bitterness (not rated) in samples of light beer with low alcohol content, as well as higher than those mentioned by Pinto et al (2015) for craft beer processed with pineapple and acerola.…”
Section: Sensory Analysiscontrasting
confidence: 75%
See 2 more Smart Citations
“…Pineapple (Ananas comosus L. Merril) belongs to the most popular group of tropical fruits in the country, thanks to its characteristic flavor and aroma. The mature fruit presents, on average, 16.2% of total soluble solids, 0.35% of citric acid, 5.06% of reducing sugars and pH 4.15, which makes it favorable for fermentative processes, such as the production of beer [8].…”
Section: Introductionmentioning
confidence: 99%